CORRELATIONS BETWEEN LANDSLIDE SCARS PARAMETERS USING REMOTE SENSING METHODS IN THE ESTRADA DE FERRO VITÓRIA-MINAS, SOUTHEASTERN BRAZIL - Denise de Fátima Santos da Silva; Rosyelle Cristina Corteletti; Roberto Almeida Cunha Filgueiras; Allan Erlikhman Medeiros Santos (Revista Brasileira de Geomorfologia, 2021)
The remote sensing has been widely used in studies involving records and monitoring landslides, also, this tool is widely used in mapping areas of geological risk. In this paper, two remote sensing methodologies were used to identify, characterize and catalog scars generated along the Estrada de Ferro Vitória-Minas (EFVM). The first methodology allowed to estimate the area and volume of landslides scars of EFVM through the images available in Google Earth Pro. The second methodology used a drone to capture the parameters in the field of landslides scars. From the obtained parameters it was possible to compare the estimates of areas and volumes of landslides by drone image with the data obtained by images of Google Earth Pro and to test the applicability of both methods. The results obtained showed estimates scars areas with correlation of 0.92 for the two methodologies. The volume estimates presented a correlation of 0.8; with underestimation of the results obtained by Google Earth Pro.